Cost and optimization in government An introduction to cost accounting, operations management and quality control - Khan, Aman (Routledge, 2017)
The careful management of costs and operations are two of the most essential elements of operating any successful organization, public or private. While the private sector is driven by profit-maximizing incentives to keep costs to a minimum, the public sector’s mission and goals are guided by a different set of objectives: to provide a wide range of essential goods and services to maintain social order, improve public health, revitalize the economy, and, most importantly, to improve the quality of life for its citizens. Although the objectives are different, it is just as important for public decision makers to make the best use of available resources by keeping the cost of operation to a minimum. This book demonstrates that with a careful emphasis on cost accounting, operations management, and quality control, all organizations and governments can increase efficiency, improve performance, and prepare to weather hard times.